Critical cases of stability of one nonautonomous essentially nonlinear equation of the nth order - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish sufficient conditions of the Lyapunov stability of the trivial solution of a nonautonomous ordinary differential equation of the nth order in the case where its characteristic equation has a multiple zero root. The stability is determined by nonlinear terms.